ナンキョク エンダービー リクチ オキ デ エタ チュウジョウ サイデイ ノ ビカセキ ブンセキ - 福島, 博; フクシマ, ヒロシ; 鈴木, 邦子; スズキ, クニコ; FUKUSHIMA, Hiroshi; SUZUKI, Kuniko (国立科学博物館, 1966)
P(論文) Microfossil analysis was made on the three cores collected in the offing of Enderby Land. The core of St. 4 was 32 cm, that of St. 7 was 38 cm and that of St. 8 was 15 cm in length. The core of St. 4 was divided into 25 materials, each being cut into approximately 1 cm pieces. The cores of St. 7 and St. 8 were divided into 36 materials and 11 materials respectively in the same way as the care of St. 4. Then, microfossil analysis was made on each material. In each material, Fragilariopsis was found dominant. It amounted to more than 90% of the total microfossils in the case of the core of St. 8, about 90% in the case of St. 7 and about 80% in the case of St. 4. F. antarctica predominated among these Fragilariopsis, occupying about 70% of the total microfossils in the case of St. 8, about 65% in the case of St. 4 and about 60% in the case of St. 7. F. antarctica was found almost uniformly, but, it suddenly decreased at a spot 26-31 cm deep from the surface. Several percent of two species of Coscinodiscus were found and the total amount of diatoms suddenly decreased at this spot only. By these reasons, it is considered that the ocean condition when the bottom deposits weie accumulated was a little different from that of other spots. However, as this change was not clear at the same spot of St. 7, no definite conclusion can be drawn from the insufficient data now available to the writers. It may be that the amount of moraine which was brought to this ocean area increased due to partial change in glacier activity. The place where the cores ware collected is free from ice-floe in midsummer, but is full of it in other seasons. Therefore, the writers considered it is either a deposits of diatoms which grow on ice-floe and color it brown, or a deposit of planktons. According to the writers' unpublished data, the dominant species which grows on ice-floe was F. cylindrus and the subdominant species was F. curta. In view of the fact that the dominant species of planktons near ice-floe was F. antarctica, it can be ...